Multi-stimuli responsive behaviors of two TPE-based tautomers in the solid state and in solution. Issue 12 (27th February 2020) - Zheng, Han-Wen; Li, Sai; Wu, Min; Kang, Yang; Li, Jia-Bin; Liang, Qiong-Fang; Zheng, Xiang-Jun; Fang, De-Cai; Jin, Lin-Pei
Abstract : Two TPE-based tautomers can respond to grinding and vapor in the solid state, and to metal ions in solution. Abstract : Multi-stimuli responsive materials have been attractive for their wide potential applications. The most important but still a challenge is the design of the material and the explanation of how the stimuli affect the molecular structure. Grinding is the most reported mechanical stimuli. But it is very difficult to obtain single-crystals directly after grinding to provide the molecular-level understanding of mechanochromic luminescence (MCL) properties because anisotropic forces can induce crystal collapse, making them unsuitable for single-crystal X-ray analysis. Here we designed a TPE-based Schiff base, N -(2-hydroxy-1-naphthylidene)-1-tetraphenylethenylamine (HL), and first obtained its enol (HL e ) and keto (HL k ) forms separately. Multi-stimuli response was realized with the aid of transformation of two tautomers. Both the tautomers can respond to grinding. The single crystal X-ray diffraction data of HL e and HL k crystals before and after grinding show that the torsion angles of HL e and HL k molecules change after grinding, which results from the variation of molecular packing and the fine-tuning of molecular conformation. The blue shift of emission bands for HL e and HL k was ascribed to the synergetic effect of crystal size and conformation variation. HL k is vapochromic and could respond to volatile organic solvents via vapor-fuming to generate HL e . This arises from proton transfer from –NH to OC of HL k, in which vapor-induced proton transfer and molecular arrangement variation play a crucial role. There exists the tautomerization of enol and keto forms in solution. HL e and HL k show aggregation-induced emission (AIE) property in THF/H2 O, but only the aggregates of HL k form could be obtained no matter whether the original solute was HL e or HL k . HL could also respond to Cu(ii ) and Al(iii ) ions in solution. It is an on–off chemosensor for Cu(ii ) and a chemodosimeter for Al(iii ) ions.